Life : my story through history [large type] - Francis, Pope, 1936-; Marchese Ragona, Fabio, 1982- (Harper Large Print, an imprint of Harper Collins Publishers, 2024)
For the first time, Pope Francis tells the story of his life as he looks back on the momentous world events that have changed history--from his earliest years during the outbreak of World War II in 1939 to the turmoil of today.